Peran Pelayanan Pastoral dalam Memotivasi Kaum Bapak Mengikuti Peribadahan Minggu di Sionggang Tengah - Hutabarat, Rut Imelda (Sekolah Tinggi Diakones HKBP, 2023)
The role of pastoral ministers has an important position in solving every problem, for example in increasing the motivation of the Fathers to attend Sunday services in Sionggang Tengah. The disinterest of the Fathers in attending Sunday services is a theological issue to be discussed. By plunging directly into the field, seeing the situation that occurred. Therefore, the role of the counselor in carrying out pastoral assistance is expected to bring about a change in the counselee's awareness of what is his basic duty as a father. This journal is a literature study and field research on pastoral care methods for fathers who rarely attend Sunday services in Sionggang Tengah. In this journal, the author criticizes the importance of reviewing mentoring methods in providing assistance to fathers who rarely attend church. Furthermore, the author also explains what practices a pastoral minister can do to improve, awaken and rebuild the wishes of the Fathers.